The combined approach to obtain approximate analytical solution of instability phenomenon arising in secondary oil recovery process - Shah, Kunjan; Singh, Twinkle (Computational & applied mathematics, 2018)
Instability phenomenon mainly occurs in secondary oil recovery process due to viscosity difference of water and oil. Mathematical modeling of this phenomenon yields the non-linear partial differential equation. The homotopy perturbation new integral transform method has been proposed to solve this non-linear partial differential equation subject to appropriate initial and boundary conditions. It is concluded that the saturation of injected water S w ( X , T ) is increasing during instability phenomenon, when length of fingers(perturbance) and time increases.